Novel early life risk factors for adult pulmonary hypertension. (April 2019) - Goss, Kara N.; Austin, Eric D.; Battiola, Therese J.; Tepper, Robert S.; Lahm, Tim
The role of perinatal insults in the development of adult onset pulmonary hypertension (PH) is unclear. We surveyed patients with and without PH for a history of early life risk factors, and identified prematurity, oxygen use, and respiratory illness each as risk predictors for development of adult PH.